Hubungan antara Pengetahuan dan Dukungan Tenaga Kesehatan dengan Perilaku Pemeriksaan Payudara Sendiri (SADARI) pada Wanita Pasangan Usia Subur (PUS) - Sari, Puspita; Sayuti, Solihin; Ridwan, M; Rekiaddin, La Ode; Anisa, Anisa (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2020)
Background. According to WHO in 2018, most cancer cases in Indonesia are breast cancer cases, with 58,256 cases out of a total of 348,809 cancer cases. Breast cancer is a disease that is at risk for women. Early detection efforts with BSE should be initiated. Objective. This study aims to determine the relationship between knowledge and support of health workers with breast self-examination behavior (BSE) on women with PUS in Bram Itam Kiri Village, Bram Itam District, Tanjung Jabung Barat Regency. Method. This research was a quantitative study with a cross-sectional design. This study involved 93 respondents who were selected using a proportional stratified random sampling technique to be interviewed. Data analysis using chi-square. Results. As many as 34.4% of respondents had bad BSE behavior. There is a significant relationship between knowledge and BSE behavior. Support from health workers did not have a significant relationship with BSE behavior. Conclusion. Respondents' understanding of BSE is still low and there is a relationship between knowledge and breast self-examination behavior (BSE).